Analisis Tata Kelola Surat Dinas Pada Bagian Umum Sekretariat DPRD Provinsi Sumatera Utara - Wiranti, Wiranti; Padli Nasution, Muhammad Irwan (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2022)
Analysis is an activity from a series of activities such as parsing, distinguishing, and sorting things to be regrouped according to certain criteria and then looking for the relationship for further study. Correspondence governance analysis is needed as a support for the smooth running of the organization or institution itself and can provide effectiveness and efficiency. Handling letters is very important for government agencies, especially in the North Sumatra Provincial DPRD Secretariat which deals with many agencies and individuals who need information from the North Sumatra Provincial DPRD Secretariat. Good letter handling will make it easier for related parties to access information what you need easily.